Respon Petani Hortikultura Terhadap Manfaat Sertifikat Prima 3 di Provinsi Aceh - Nupudiya Nupudiya; Ainal Mardhiah; Khumaira Khumaira; Teuku Fadhla; Rahmiati Rahmiati; Mulyadi Mulyadi (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
Prima 3 certificate is a labeling of fruit and vegetable agricultural products in ensuring food safety with the aim of providing quality assurance and food safety. Aceh Province has used Prima 3 Certification which is given to companies or farmers who cultivate Horticultural crops that are free of pesticide residues. The purpose of the study was to determine the response of horticultural farmers to prime 3 certification in Aceh province. The data analysis model used is Likert scale analysis and Spearman rank correlation analysis. Based on the results of the study, it shows that the response of farmers to the benefits of prime 3 certification in Aceh Province is 66%, which means that they are in the agreed category because in terms of relative benefits they get high income, in terms of the level of conformity of the product composition standards in accordance with technical requirements, from the level of complexity of administrative requirements is very easy to fulfill, registration is easy to implement, in terms of easy application, the quality of the product is better, the product is safer from chemicals, and safe for consumption, so in terms of innovation it is easy to observe. Spearman rank correlation results age, education, experience have a high relationship with farmer response, while land area has a low relationship